Practise of knowledge management among employees in Bank Rakyat Jasin / Noorhidayah Idris - Idris, Noorhidayah (Faculty of Business and Management, 2010)
This study will cover the critical success factors of knowledge management practices in Bank Rakyat Jasin. Bank Rakyat Jasin has been chosen as a study setting in order to analyze this topic. Knowledge management is considered to be important for organizational success in the contemporary world, as now knowledge is now accepted as a critical resource. Moreover, in spite of the importance of knowledge asset, how knowledge is generated is still an unknown factor. This study will be based on what are the critical success factors that can influence the knowledge management in Bank Rakyat Jasin. One of the factors is people which can directly affect the implementation of knowledge management. The result shows that they are also strongly agreed that they must learn to share knowledge and accept information in order to improvise the job performed, skills and abilities as well. In addition, when knowledge is being shared and transferred among them, it will increase the collaboration between employees. A second factor is organization processes and structures. When there are established procedures for tasks in the bank, it provides a path to transform the acquired knowledge as well as reducing the work ambiguity in each of the employee. Another third factor is technology which can be considered as one of the crucial factors that may contribute towards the successful of knowledge management among employees. The technology systems should be accessible so that it can smooth the process of learning among the employees. Today’s business environment is characterized by highly transparent market and global competition. Technology lifecycle is decreasing due to the fast pace at which development of new technologies is progressing at the rapid pace. Fourth factor is adequacy of training. Bank Rakyat is continuously taking steps to aid in career growth opportunities for its employees. Through training, the employees can acquire knowledge that relates to their tasks. It is undeniable that training can lead to career development of the employees as well as for the benefit of the bank. Thus, the study has revealed that Bank Rakyat Jasin have all the factors that contributes to the knowledge management practice. Several recommendations have been proposed in order to enhance the practice so that all the employees will be well-equipped with the knowledge that exists around them.